Production and molecular characterization of tailored citrus pectin-derived compounds. (15th January 2022) - Humerez-Flores, Jessika N.; Kyomugasho, Clare; Gutiérrez-Ortiz, Ana A.; De Bie, Margot; Panozzo, Agnese; Van Loey, Ann M.; Moldenaers, Paula; Hendrickx, Marc E.
Graphical abstract: HPSEC-RI-MALLS: High Pressure Size Exclusion Chromatography/Refractive Index detection and Multi Angle Laser Light Scattering; FT-IR: Fourier Transformed Infrared Spectroscopy; ICP-OES: Inductively Coupled Plasma Optical Emission Spectrometry; HPAEC-PAD: High-Performance Anion-Exchange Chromatography with Pulsed Amperometric Detection; ESI/TOF-MS: Electrospray ionization-time-of-flight- -mass spectrometry. Highlights: A diversity of citrus-pectin derived samples were successfully generated through enzymatic and chemical processes. The generated pectin molecules exhibited differences in structure, including molecular weight and degree of methylesterification. The pectin-derived samples generated contained different fractions of oligosaccharides of degree of depolymerization between 1 and 6. Abstract: In this study, tailored-made citrus pectin-derived compounds were produced through controlled enzymatic and/or chemical modifications of commercial citrus pectin with different degrees of methylesterification (DM) and similar average molecular weight (MW ). In the first treatment, degradation of the citrus pectin (CP) materials by endo -polygalacturonase (EPG) yielded pectins with average Mw 's (between 2 and 60 kDa). Separation and identification of the oligosaccharide fraction present in these samples, revealed the presence of non-methylesterified galacturonic acid oligomers with degree of polymerization (DP) 1–5. In the second treatment, exploiting the combined effect of EPG and pectin lyase, compounds with MW between 2 and 21 kDa, containing methylesterified and non-methylesterified polygalacturonans (DP 1–6), were generated. Finally, CP was sequentially modified by chemical saponification and the action of EPG. A sample of DM 11% and MW 2.7 kDa, containing POS (DP 1–5), was produced. Diverse pectin-derived compounds were successfully generated for further studies exploring their functionality.